Hubungan Pemberian Imunisasi Dasar dengan Status Gizi Pada Anak Usia 1 - 3 Tahun - Raisyah Aprili Sarinda; Trisonjaya Trisonjaya; Bambang Eko Supriyanto (Malahayati Nursing Journal, 2023)
ABSTRACT One of the efforts to prevent infectious diseases is by giving immunization infants and toddlers. Immunization is one of the factors that affect the body's resistance to various diseases or immunity, which will influence an anthropometric nutritional status and child survival. To determine the relationship between basic immunization and nutritional status in children aged by 1-3 years old. The design of this research is using correlational quantitative with cross sectional design. The number of samples is 114 children aged by 1-3 years old using purposive sampling technique. The results of the univariate analysis showed that most of the children aged by 1-3 years old in Citangkil II Community Health Center (Puskesmas) in Cilegon City were given complete basic immunization (78.1%) and had good nutritional status (71.9%). The results of the bivariate analysis obtained p value: 0,001, it means there is relationship between the provision of basic immunization and the nutritional status of children by aged 1-3 years old. There is a relationship between basic immunization and nutritional status in children aged by 1-3 years old.  Keywords: Immunization, Nutritional Status, Toddler  ABSTRAK Salah satu upaya pencegahan penyakit infeksi adalah dengan pemberian imunisasi pada bayi dan balita. Imunisasi merupakan salah satu faktor yang mempengaruhi daya tahan tubuh terhadap berbagai penyakit atau kekebalan tubuh yang selanjutnya akan berpengaruh pada status gizi antropometri dan survival anak. Untuk mengetahui hubungan pemberian imunisasi dasar dengan status gizi pada anak usia 1-3 tahun.  Desain penelitian adalah kuantitatif korelasional dengan desain cross sectional. Jumlah sampel adalah 114 anak usia 1-3 tahun diambil dengan menggunakan teknik purposive sampling. Hasil analisis univariat menunjukkan anak usia 1-3 tahun di Puskesmas Citangkil II Kota Cilegon sebagian besar memiliki status gizi baik (71,9%) dan sebagian besar diberikan imunisasi dasar lengkap (78,1%). Hasil analisis bivariat didapatkan nilai p: 0,001, hal tersebut berarti ada hubungan antara pemberian imunisasi dasar lengkap dengan status gizi pada anak usia 1-3 tahun. Ada hubungan antara pemberian imunisasi dasar lengkap dengan status gizi pada anak usia 1-3 tahun di Wilayah Kerja Puskesmas Citangkil II Kota Cilegon. Kata Kunci: Balita, Status Gizi, Perkembangan